Evaluation of Recent Techniques in Diagnosis of Induced Caprine Pneumonia - Abdullah, Shimaa M.; El-Sheikh, Abdel Khalek R.; Mahmoud, Abdel Raouf M.; Attia, Noura E.; El-Seddawy, Nora (Journal of Advanced Veterinary Research, 2022)
The goal of the current study was to assess the new techniques for diagnosing of ammonia-induced pneumonia in goats, primarily using radiography and CT examinations coupled with some selective biochemical parameters. The experimental induction of pneumonia using ammonia vapor inhalation (33%), was performed on five female goats weighing 20 to 30 kg and ranging in age from 10 months to one year. A thorough clinical examination was performed on all goats. Goats' jugular veins were used to collect blood samples in order to monitor changes in the pulmonary function test and some selective biochemical parameters. A clinical examination of goats showed that exposure resulted in a significant (P< 0.05) rise in mean rectal temperature at day 14, as well as heart and respiration rates at day 7. On the 7th day, dullness, coughing, dyspnea, bilateral mucopurulent or mucoid/purulent nasal discharge, and abnormal lung auscultation were recorded. On 14th day, the severity increased. When compared to zero-day results (auto-control group), serum biochemical examination showed significant (P< 0.05) increases in Hp, SAA at 7 days, and MDA levels at 14 days, but there was a significant (P< 0.05) decrease in TAC at 14 days after inhalation. When ammonia was inhaled, pCO2, tCO2, pO2, and HCO3 changed significantly (P< 0.05) at day 7 and pH decreased significantly at day 14. Upon ultrasonography, pneumonic consolidation displays an echotexture resembling the liver with the presence of hypoechoic patches and loss of reverberation artefacts. The chest x-ray showed increased opacity (more gray or white) with a cotton-wool-like look. On the 7th day, a lung CT revealed focused areas of ground-glass opacity that later became diffuse. An edematous, hyperemic lung with consolidation was observed during the postmortem examination. Lung histopathology revealed serofibrinous pneumonia. Therefore, in order to diagnose ammonia-induced pneumonia in goats, ultrasonographic, radiographic, and CT examinations, coupled with selective biochemical parameters and pulmonary function tests, are useful.